Effect of mangrove leaves extract (avicennia marina) concentration to streptococcus mutans and candida albicans growth - Mohammad Dharmautama; Richard Tetelepta; Muhammad Ikbal; Andi EA. Warti (Journal of Dentomaxillofacial Science, 2017)
Objective: This study aims to determine the effect of mangrove leaves extract (avicennia marina) concentration to streptococcus mutansandcandida albicansgrowth which is commonly found in removable denture plate.Material and Methods: Production of mangrove leaves extract (avicennia marina) using 96% ethanol solution. Mangrove leaves extract prepared at a concentration of 2.5%, 5%, 7.5%, 10% and control with denture cleaning materials available in the market. Furthermore, tested the bacteria activity ofstreptococcusmutans and candida albicans, then the data were analyzed by One Way ANOVA and Post Hoc Test (Tukey HSD).Results: Statistical analysis of mangrove leaves extract with 2.5% concentration (6.850 ± 0.127), 5% (7.185 ± 0.007), 7.5% (8.360 ± 0.283), 10% (8.485 ± 0.219) and positive control (9.060 ±0.226), showed inhibition zone differences are significant (p<0.05). The concentration of 7.5% had optimal inhibition of the growth ofstreptococcusmutans (p<0.05). Mangrove leaves extract to 10% concentration had not shown the effects of inhibition zone against candida albicans.Conclusion: Mangrove leaves extract (avicennia marina) is effective in inhibiting the growth of streptococcus mutans but hasn’t shown inhibition zone against candida albicans until 10% concentration.